Multiple jejunal gastrointestinal stromal tumors and Neurofibromatosis type 1: A rare association - Mishra, Aakash (Int J Surg Case Rep, 2021)
INTRODUCTION AND IMPORTANCE: The association between gastrointestinal stromal tumor (GIST), mesenchymal tumor arising from the interstitial cells of cajal and Neurofibromatosis type 1 (NF1), an autosomal dominant disease has been reported in the literature. GIST in NF1 patients are multiple and located in the small intestine. Tumorigenesis in NF1 associated GIST is different to that of sporadic GIST and hence the treatment. Here we report a rare case of an NF1 patient with multiple jejunal GISTs. CASE PRESENTATION: We here present a rare case of a 57-year-old male diagnosed with NF1 30 years back, presented in our emergency department with complaints of black, tarry stools later diagnosed to have multiple GIST in jejunum. Contrast enhanced computed tomography (CECT) of the abdomen showed a large 10.1 × 7.33 × 6.2 cm heterogeneous, exophytic, solid mass with cystic areas originating from the jejunum. The microscopic examination of the specimen showed spindle shaped tumor cells while immunohistochemistry showed CD117 (c-KIT) and DOG-1 positivity. The primary treatment was complete surgical excision of the tumor. CLINICAL DISCUSSION: The incidence of GISTs in NF1 patient is around 6–7%; however, concomitant presence of multiple GISTs is rare. CECT of abdomen along with histopathological and immunohistochemistry studies are diagnostic. The management of GIST includes surgical and adjuvant therapy methods based on the tumorigenesis and recurrent risk stratification. CONCLUSION: Early clinical suspicion and imaging aids in early detection of the tumor in patients with NF1 presenting with gastrointestinal symptoms. Postoperatively, screening for recurrence with radiology is of utmost importance.